2004
DOI: 10.1016/j.geoderma.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Organic inputs and farmers' management strategies in millet fields of western Niger

Abstract: Research on soil fertility management in sub-Saharan Africa was criticized lately for largely ignoring farmers' management strategies and the underlying principles. To fill this gap of knowledge, detailed interviews were conducted with 108 farm households about their rationale in managing the soil fertility of 307 individual fields in the agro-pastoral village territory of Chikal in western Niger. To amplify the farmers' information on manuring and corralling practices, repeated measurements of applied amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…However, even at higher faecal N-contents, undigested cell walls in faeces were supposed to be responsible for the observed temporary immobilization of mineral soil nitrogen ͑De Ridder and Van Keulen 1990;Powell et al 1999͒. Allowance for seasonal differences in the decomposition and mineralisation of applied organic matter must also be made when considering an intermediate time scale: the disappearance of manure is faster during the wet and the cool dry season than during the hot dry season, and is affected by soil temperature, rainfall and soil moisture ͑Somda et al Esse et al 2001;Schlecht and Buerkert 2004͒. Due to the manifold factors accelerating or decelerating manure decomposition, Somda et al ͑1995͒ were concerned about the uncertain timing of nutrient release. On the other hand, Powell et al ͑1999͒ welcomed the initial fixation of a certain portion of mineral N in the coarse SOM fraction after mulching or manuring, and suggested that the subsequent mineralisation would synchronize N-release with plant demand.…”
Section: Nutrient Inputs Through Organic Material: Effects Of Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, even at higher faecal N-contents, undigested cell walls in faeces were supposed to be responsible for the observed temporary immobilization of mineral soil nitrogen ͑De Ridder and Van Keulen 1990;Powell et al 1999͒. Allowance for seasonal differences in the decomposition and mineralisation of applied organic matter must also be made when considering an intermediate time scale: the disappearance of manure is faster during the wet and the cool dry season than during the hot dry season, and is affected by soil temperature, rainfall and soil moisture ͑Somda et al Esse et al 2001;Schlecht and Buerkert 2004͒. Due to the manifold factors accelerating or decelerating manure decomposition, Somda et al ͑1995͒ were concerned about the uncertain timing of nutrient release. On the other hand, Powell et al ͑1999͒ welcomed the initial fixation of a certain portion of mineral N in the coarse SOM fraction after mulching or manuring, and suggested that the subsequent mineralisation would synchronize N-release with plant demand.…”
Section: Nutrient Inputs Through Organic Material: Effects Of Timementioning
confidence: 99%
“…Manure accumulating at the homestead overnight is mixed with feed residues and household waste and transported to selected fields ͑Harris 1998; Schlecht and Buerkert 2004͒. Alternatively, corralling own or contracted livestock on the selected fields reduces labour and costs for transport and, through the direct recycling of faeces and urine to the targeted spot also reduces losses of nutrients, particularly nitrogen ͑Powell et al Hoffmann et al 2001;Schlecht and Buerkert 2004͒. Across five village territories in Western Niger, herds of approximately 25-60 animals were reported to spend between 15 and 46 nights on one field, thereby depositing 3.4-15.5 t ha -1 of faecal dry matter in the case of cattle and 1.3-7.2 t ha -1 in the case of small ruminants ͑Schlecht et al 2004͒.…”
Section: Livestock-mediated Nutrient Transfers: Effects Of Managementmentioning
confidence: 99%
“…However, 500-1000 kg ha À1 of post-harvest millet was not always effective in reducing soil flux. Although mulching with a large quantity of post-harvest millet residue is effective, application of 1500 to 2000 kg ha À1 is not realistic in the Sahel because the productivity of very sandy soils is too low and millet residue is extensively used as animal feed, fuel, and constructing material (Lamers and Feil 1993;Michels et al 1995b;Schlecht and Buerkert 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This does not mean that farmers are ignorant of wind-erosion problems. Studies in Niger showed that most farmers recognize the severe damage caused by wind erosion, are aware of wind erosion control techniques, and many have even tried to apply one or several of these techniques (Taylor-Powell 1991;Sterk and Haigis 1998;Bielders et al 2001;Schlecht and Buerkert 2004). The main reason for non-adoption may be that developers and/or extension workers of these techniques did not give sufficient attention to their practicality for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…So little crop residues are left on farms. Schlecht and Buerkert (2004) found in a recent survey in Chikal territory, southwestern Niger that mulching of crop residues was mainly practiced to fight wind erosion but was restricted to 36% of 307 individual farmers' fields given the alternative uses of straw. Quantities of stover found on farms in the Sahel before millet sowing are less than 800 kg ha -1 and mostly inadequate for effective mulching (Baidu-Forson, 1995).…”
Section: Crop Residuesmentioning
confidence: 99%